Diagnostics and therapy in nephrology – guidelines and recommendations - Czekalski, Stanisław (Przewodnik Lekarza/Guide for GPs, 2007)
Actual clinical practice guidelines and recommendations in kidney diseases indicate the need for early diagnosis of both acute and chronic kidney disease (CKD) and for intensive treatment from the earliest stage of the disease. The role of family doctors and specialists in internal diseases, diabetology, hypertensiology and cardiology in early diagnosis of CKD is of particular importance. The most important principles of the management of patient with CKD were discussed. The team cooperation of physicians of different specialities is the only way to reduce the increasing number of patients who need expensive renal replacement therapy.